Effect of calcium peroxide on the water quality and bacterium community of sediment in black-odor water. (May 2019) - Wang, Wen-Huai; Wang, Yi; Fan, Pan; Chen, Lin-Feng; Chai, Bao-Hua; Zhao, Jing-Chan; Sun, Lu-Qin
Abstract: This study investigated how efficiently CaO2 could treat black-odor landscape water caused by low dissolved oxygen (DO) in a field experiment of 600 m 2 . The study demonstrated that CaO2 could significantly elevate the DO concentration in waters and the oxidation–reduction potential (ORP) level in sediments (p = 0.003 and p = 0), which is conducive to improving the anoxic environment of landscape water. The concentrations of total chemical oxygen demand (TCOD) and S 2− in overlying and interstitial waters were considerably decreased. The average concentrations of TCOD in the overlying and interstitial waters of the test zone (TZ) were 52.98% and 66.05% of those of the control zone (CZ), and the average concentrations of S 2− in the overlying and interstitial waters of TZ were 29.63% and 39.79% of those of CZ. Meanwhile, CaO2 could obviously reduce turbidity but increase the transparency in the overlying water. The mean value of turbidity in the overlying water of TZ was 39.46% of that of CZ, whereas the transparency in the overlying water of TZ was 2.07 times that of CZ. Furthermore, CaO2 changed the microbial community structure in the sediments, where the relative abundance of anaerobic bacteria was decreased but that of the aerobic bacteria was increased with some functional bacteria. In summary, CaO2 could significantly increase the DO and ORP in black-odor landscape water, obviously inhibit the release of pollutants from sediment, and increase the diversity of microbial strains. Consequently, the black-odor phenomenon of landscape water could be alleviated effectively by adding CaO2 . Graphical abstract: Image 1 Highlights: Effect of CaO2 on black-odor landscape water was firstly studied in a field test. CaO2 could elevate DO and ORP, thereby effectively improved the anoxic environment. CaO2 could derive some functional species such as Nitrobacter and Thiobacillus. CaO2 reduced pollutants concentrations by enhancing biological action in sediment. CaO2 reduced turbidity 60.54%, TCOD 47.02% and S 2− 70.37% in the overlying water. Abstract : This paper could provide an effective reference for the management of black-odor landscape water and demonstrate an important field case for similar problems.